2012
DOI: 10.1002/j.0022-0337.2013.77.2.tb05454.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Evidence‐Based Guidelines in Dentistry

Abstract: Use of guidelines is an important means of reducing the gap between research and clinical practice. Sound and unbiased information should be available to enable dental professionals to provide better clinical treatment for their patients. The development of clinical guidelines in dentistry should follow standard and transparent methodology. The purpose of this article is to propose important steps for developing evidence-based clinical recommendations in dentistry. Initially, dental guidelines should be extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Moreover, the present study showed that only half of the respondents expressed a need for new evidence‐based national guidelines regarding population‐based preventive interventions. Evidence‐based practice guidelines are a new tool to update clinicians in their work and they are developed by multidisciplinary working groups and based on systematic reviews of research . Internationally, an evidence‐based dentistry approach to individual patient care and service planning has been in focus for several years, but the professionals in the present study seemed to be rather self‐confident and did not have a positive attitude towards such an approach.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the present study showed that only half of the respondents expressed a need for new evidence‐based national guidelines regarding population‐based preventive interventions. Evidence‐based practice guidelines are a new tool to update clinicians in their work and they are developed by multidisciplinary working groups and based on systematic reviews of research . Internationally, an evidence‐based dentistry approach to individual patient care and service planning has been in focus for several years, but the professionals in the present study seemed to be rather self‐confident and did not have a positive attitude towards such an approach.…”
Section: Discussionmentioning
confidence: 78%
“…The results of this study indicate that various common clinical dental procedures such as the use of pit and fissure sealants currently do not have too many specifically and free‐access clinical guidelines. This is a cause for concern, because clinical guidelines are supposed to be an important tool for effective evidence‐based dental practice, and consequently, their development should be targeted to a large number of commonly performed procedures .…”
Section: Discussionmentioning
confidence: 99%
“…1 High-quality, evidence-based clinical practice guidelines offer a mode of bridging the gap between policy, best practice, local contexts and patient options, 1,2 support effective clinical practice and bring potential benefits to practitioners and patients. 5,6 They get research into practice by providing the link, reducing the gap between evidencebased literature and clinical practice, and providing users with consistent advice and common points of reference for assessing their performance against measurable criteria. 6,7 While CGs are mainly developed to support and assist clinicians and patients, they can also help to improve and monitor patient safety, clinical effectiveness, and quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 They get research into practice by providing the link, reducing the gap between evidencebased literature and clinical practice, and providing users with consistent advice and common points of reference for assessing their performance against measurable criteria. 6,7 While CGs are mainly developed to support and assist clinicians and patients, they can also help to improve and monitor patient safety, clinical effectiveness, and quality of care. 8 Improved quality of care, efficiency and cost containment, 9 reduced morbidity and mortality, 10 increased patient knowledge and awareness on treatment about benefits and harm of various treatments, 5,7 are all listed as goals and benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation